PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SDN INPRES VIM 2 KOTARAJA - Warikar, Amelia; Dian Septikasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading comprehension is a fundamental skill in elementary education as it determines students’ academic success across subjects. However, classroom observations at SDN Inpres VIM 2 Kotaraja indicated that fourth-grade students experienced difficulties in identifying main ideas, making inferences, and drawing conclusions from texts, which reflects the need for more engaging and student-centered learning approaches. This study aimed to examine the effect of the Problem Based Learning (PBL) model on students’ reading comprehension skills. The research employed a quantitative approach using a quasi-experimental nonequivalent control group design. The participants consisted of 30 students in the experimental class and 28 students in the control class. The instrument was a reading comprehension test covering indicators of identifying main ideas, understanding explicit information, making inferences, and concluding text content. The instrument demonstrated high reliability with a Cronbach’s Alpha coefficient of 0.84. Data were analyzed using normality tests, homogeneity tests, and an independent sample t-test at a significance level of 0.05. The findings revealed a significant difference between the experimental and control groups (t = 5.77; p < 0.001), with the experimental group achieving higher posttest scores. These results indicate that the Problem Based Learning model significantly improves students’ reading comprehension skills and supports the implementation of student-centered learning in the Merdeka Curriculum framework